Taxonomic treatment of the tribe Mutisieae (Asteraceae) in Mexico - Redonda Martínez, Rosario (Instituto de Ecología, A.C., 2018)
Background and Aims: The tribe Mutisieae includes 14 genera and about 200 species distributed mainly in South America; it comprises several taxa of Asteraceae with bilabiate corollas and heterogamous heads with trimorphic or dimorphic florets. The aim of this work is providing an updated taxonomic treatment of the tribe in Mexico.Methods: A bibliographic review of several taxonomic studies of the Mutisieae genera present in Mexico was carried out, and online collections and some scientific collections were consulted, in order to generate the list of Mexican Mutisieae as well as identification keys and descriptions of members of the tribe.Key results: In Mexico, the tribe Mutisieae is represented by four genera and 16 species, nine of which are endemics. Chaptalia is the most diverse with 12 species, followed of Leibnitzia with two, while Adenocaulon and Gerbera are represented by one taxon each one.Conclusions: The specific richness of Mutisieae in Mexico is limited; however, the endemism level is considerable, as the nine taxa restricted distribution to the country represent 56.25% of total Mexican Mutisieae. The 12 species of Chaptalia are equivalent to 30% of the genus; the seven endemic taxa correspond to 58.33% of the diversity of the tribe, which occurs in the national territory.